The Use of Nanoparticles in Otoprotection - Barbara, Maurizio; Margani, Valerio; Covelli, Edoardo; Filippi, Chiara; Volpini, Luigi; El-Borady, Ola M.; El-Kemary, Maged; Elzayat, Saad; Elfarargy, Haitham H. (Frontiers in Neurology, 2022)
The inner ear can be insulted by various noxious stimuli, including drugs (cisplatin and aminoglycosides) and over-acoustic stimulation. These stimuli damage the hair cells giving rise to progressive hearing loss. Systemic drugs have attempted protection from ototoxicity. Most of these drugs poorly reach the inner ear with consequent ineffective action on hearing. The reason for these failures resides in the poor inner ear blood supply, the presence of the blood-labyrinthine barrier, and the low permeability of the round window membrane (RWM). This article presents a review of the use of nanoparticles (NPs) in otoprotection. NPs were recently used in many fields of medicine because of their ability to deliver drugs to the target organs or cells. The studies included in the review regarded the biocompatibility of the used NPs by in vitro and in vivo experiments. In most studies, NPs proved safe without a significant decrease in cell viability or signs of ototoxicity. Many nano-techniques were used to improve the drugs' kinetics and efficiency. These techniques included encapsulation, polymerization, surface functionalization, and enhanced drug release. In such a way, it improved drug transmission through the RWM with increased and prolonged intra-cochlear drug concentrations. In all studies, the fabricated drug-NPs effectively preserved the hair cells and the functioning hearing from exposure to different ototoxic stimuli, simulating the actual clinical circumstances. Most of these studies regarded cisplatin ototoxicity due to the wide use of this drug in clinical oncology. Dexamethasone (DEX) and antioxidants represent the most used drugs in most studies. These drugs effectively prevented apoptosis and reactive oxygen species (ROS) production caused by ototoxic stimuli. These various successful experiments confirmed the biocompatibility of different NPs and made it successfully to human clinical trials.